2017
DOI: 10.1002/adma.201606464
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Device Physics in Polymer‐Based Ionic–Organic Ratchets

Abstract: High-performance solution-processed ionic-organic ratchets are fabricated using polymer semiconductors. The devices can provide both high short-circuit current and open-circuit voltage at room temperature, and be driven by AC signals with frequencies up to 13.56 MHz. The effects of trap density, mobility, and rectification ratio in the device on short-circuit current are investigated and clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Likewise conductive polymers can be used as ion pumps to control spatial and temporal ion movement, with applications to drug delivery 5 , 6 . A number of other electrochemical energy-conversion and storage devices have been realized using conductive polymers, including organic electronic ratchets 7 9 , redox-flow batteries 10 , 11 , supercapacitors 12 , 13 , electrochromics 14 , 15 , and (photo-)electrochemical cells for catalysis and water purification 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise conductive polymers can be used as ion pumps to control spatial and temporal ion movement, with applications to drug delivery 5 , 6 . A number of other electrochemical energy-conversion and storage devices have been realized using conductive polymers, including organic electronic ratchets 7 9 , redox-flow batteries 10 , 11 , supercapacitors 12 , 13 , electrochromics 14 , 15 , and (photo-)electrochemical cells for catalysis and water purification 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This ion redistribution provides the rectifying function of the ratchet, similar to the mechanism proposed for ionic-organic ratchets. [7,10] Thus, the operation of the perovskite electronic ratchet under a time-averaged zero-bias gate signal and zero source-drain bias can be described as such. When the negative voltage bias of the input signal is applied to the gate electrode, holes will accumulate in the channel from the source electrode, although the large V oc (vide supra) suggests that there may also be some injection from the drain electrode.…”
Section: Resultsmentioning
confidence: 99%
“…In the most popular incarnation of the organic electronic ratchet, an asymmetric potential distribution is developed directly within a chemically doped organic semiconductor by applying a voltage stress. [ 7,10–13 ] While this effect is purported to arise from the electric‐field‐induced redistribution of ions, [ 14 ] direct evidence for ion movement is rarely observed. The exploitation of ion motion in “soft” materials suggests that hybrid organic–inorganic lead‐halide perovskites (LHP), where ion motion is known to be relatively facile, [ 15–21 ] represent potential alternative semiconductor materials for electronic ratchet devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this background, here we report a systematic study on the thermoelectric properties of a typical high‐mobility D–A copolymer semiconductor poly[4‐(4,4‐dihexadecyl‐4H‐cyclopenta[1,2‐b:5,4‐b′]dithiophen‐2‐yl)‐alt‐[1,2,5]thiadiazolo[3,4‐c]pyridine] (PCDTPT, molecule structure in Figure a) to reveal the potential of D–A copolymers for OTE applications. In conjunction with PCDTPT, an organic salt trityl tetrakis(pentafluorophenyl) borate (TrTPFB, molecule structure in Figure 1b) was employed for doping as it has been reported to p‐dope PCDTPT by a simple solution‐blending method in our previous works 37,38. By varying the doping concentrations, the characteristic parameters of thermoelectric materials such as σ, S and κ were investigated in the temperature range of room temperature (RT ≈ 300 K) to 400 K. It is found that the 5 wt% doped semiconductors have the maximum PF of 7 µW K −2 m −1 with electrical conductivities approaching 4 S cm −1 and Seebeck coefficients of ≈150 µV K −1 .…”
mentioning
confidence: 99%